Modelling long-term changes in soil phosphorus and carbon under contrasting fertiliser and grazing management in New Zealand hill country - Bilotto, Franco (2019)
Soil carbon (C) stocks under permanent New Zealand pastures vary with slope and aspect due to differences in primary production, animal behaviour and nutrient return. An existing nutrient transfer model was extended using a web-based, general-purpose modelling tool to simulate long-term changes in soil phosphorus (P) and C in hill country under contrasting fertiliser and sheep stocking regimes. Three self-contained farmlets were examined: no P applied; 125 kg single superphosphate (SSP)/ha/year; and 375 kg SSP/ha/year, since 1980. The refined spatial model was able to simulate P and C distribution with varying slopes and aspects. For example, the mean annual changes in soil P and C were greater on low slopes and eastern aspects than on the other two slope and aspect positions, consistent with observed changes in these nutrients. However, the model overestimated changes in soil C, which highlighted both gaps in current knowledge and key factors influencing change in soil C stocks. Understanding the spatial patterns of soil C across the landscape will be critical in the design of soil C monitoring regimes, should soil C stocks be considered at a national level as a sink or source of CO2 emissions.